Increasing CLEI 6 students’ vocabulary through the use of Moodle resources and activities (2017)
ABSTRACT: This action research study was designed aiming to increase the vocabulary of students in CLEI6 - educational program for adults – through the use of the resources and the developing the activities designed in a Moodle platform, in a public institution in Medellin, Colombia. Data were collected through reflective logs and the use of different students’ artifacts Analysis of data revealed that, the use this platform with its multiple resources and activities helped to increase the students’ vocabulary, which contributed to improve their language learning process.